Evaluation of overland flow modelling hypotheses with a multi‐objective calibration using discharge and sediment data. Issue 12 (1st December 2022) - de Lavenne, Alban; Lindström, Göran; Strömqvist, Johan; Pers, Charlotta; Bartosova, Alena; Arheimer, Berit
Abstract: Conceptual hydrological models can move towards process‐oriented modelling when addressing broader issues than discharge modelling alone. For instance, water quality modelling generally requires understanding of both pathways and travel times which might not be easily identified because observations at the outlet aggregate all processes at the catchment scale. In this study we tested if adding a second kind of observation, specifically sediment data, can help distinguish overland flow from total discharge. We applied a multi‐objective calibration on both discharge and suspended sediment concentration simulation performance to the World‐Wide Hydrological Predictions for the Environment (HYPE) model for 111 catchments spread over the USA. Results show that in comparison to two calibrations made one after the other, the multi‐objective calibration leads to a significant improvement on the simulation performance of suspended sediments without a significant impact on the performance of discharge. New modelling hypotheses for overland flow calculations are proposed and resulted in similar discharge performances as the original one but with fewer parameters, which reduces equifinality and can prevent unwarranted model complexity in data‐poor areas. Abstract : Suspended sediment concentrations can be used as a proxy to better identify overland flow. A multi‐objective calibration of the HYPE hydrological model, jointly on river discharge and suspended sediment concentrations, allows improving sediment simulation without impacting river discharge and to propose new routines for overland flow modelling.